2017
DOI: 10.1371/journal.pone.0183334
|View full text |Cite
|
Sign up to set email alerts
|

Circulating miRNAs in sepsis—A network under attack: An in-silico prediction of the potential existence of miRNA sponges in sepsis

Abstract: Biomarkers based on the molecular mechanism of sepsis are important for timely diagnosis and treatment. A large panel of small non-coding microRNAs was reported to modulate the immune response in sepsis but have not been tested in clinical practice. Large-scale identification of microRNA networks in sepsis might reveal a new biological mechanism that can be also targeted by gene therapy. Therefore, the main objective of this study is to perform a comparison of the miRNA network between septic patients and heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 49 publications
1
33
0
1
Order By: Relevance
“…The same phenomenon has been observed in the case of microRNAs (63) and circulating proteins (64). One possible solution to overcome this issue of low specificity is to analyze more than one circulating molecule and build networks with direct and indirect interactions between the molecules (65,66). Another solution is to integrate the membrane proteins of exosomes in the diagnostic algorithm.…”
Section: Final Remarksmentioning
confidence: 99%
“…The same phenomenon has been observed in the case of microRNAs (63) and circulating proteins (64). One possible solution to overcome this issue of low specificity is to analyze more than one circulating molecule and build networks with direct and indirect interactions between the molecules (65,66). Another solution is to integrate the membrane proteins of exosomes in the diagnostic algorithm.…”
Section: Final Remarksmentioning
confidence: 99%
“…As a second approach for identifying the functionally most relevant miRNAs among the 23 found to be differentially expressed by microarray, we built an expression network for these miRNAs (37). This represents a high-level correlation between the miRNA expression in a given group of patients and is composed of nodes (the miRNAs) and of edges (high correlations between the expression of 2 miRNAs) (38,39). The miRNA network of nonresponders is far more connected compared with responders ( Figure 1C): it contains 104 edges, being a well-connected network with 14 nodes with over 10 edges each (nodes with high node connectivity, 0.4783-0.6087).…”
Section: Resultsmentioning
confidence: 99%
“…11 Reports have denoted that miRNAs participate in the progression of sepsis. 12,13 Researches have suggested that miR-192-5p was diminished in some tumors such as lung cancer, bladder carcinoma, and so on. 14,15 Instead, miR-192-5p function in the pathophysiological process of sepsis needs further exploration.…”
Section: Impact Statementmentioning
confidence: 99%